ANALISIS PENERAPAN PSAK NO 105 TERHADAP PEMBIAYAAN MUDHARABAH PADA KSPPS BMT ISTIQLAL KOTA PEKALONGAN - M. Iqbal Notoatmojo; Rizka Ariyanti (Politeknik Negeri Semarang, 2022)
This study aims to determine the application of accounting treatment for mudharabah financing carried out by KSPPS BMT Istiqlal Pekalongan City based on PSAK No. 105 which includes recognition, measurement, presentation and disclosure. This study uses qualitative data, and the data sources used are primary data and secondary data. The method used is descriptive qualitative method and data collection techniques by means of field studies (observations and interviews) and documentation. Based on the results of the analysis, it can be concluded that the accounting treatment of mudharabah financing at KSPPS BMT Istiqlal Pekalongan City which includes (1) accounting recognition of mudharabah financing which consists of profit recognition and expense recognition has implemented PSAK no. 105. However, for the recognition of investments, the recognition of losses in the form of non-cash assets and the recognition of receivables have not applied to PSAK No. 105. (2) Accounting measurement of mudharabah financing has not fully implemented PSAK No. 105. The measurement of investment in the form of non-cash assets has not applied to PSAK No. 105. (3) The presentation of accounting for mudharabah financing has implemented PSAK No. 105. (4) Accounting disclosures for mudharabah financing have implemented PSAK No. 105